Hip Fractures in Malta: Are we Missing an Opportunity? - Bugeja, Mark; Curmi, Arthur; Desira, Daniel; Bologna, Gregory Apap; Galea, Francesco; Esposito, Ivan (The Surgery Journal, 2021)
Introduction Osteoporosis is a bone disease that is both preventable and treatable. It usually becomes evident when a fragility fracture occurs. Unfortunately, most studies show that only a small percentage of individuals at increased risk of fracture are assessed and treated, even following a fragility fracture.Objective The aim of this study was to determine whether patients suffering from a low-energy hip fractures in the Maltese Islands are given osteoporosis treatment.Method All patients older than 50 years presenting to the acute care hospitals in Malta and Gozo with a fragility hip fracture during December 1, 2015 and November 30, 2016 were included. Data on mortality, other fragility fractures, prescription of calcium, vitamin D, and antiresorptive therapy were collected.Results Calcium with vitamin D supplements were prescribed to 40% of patients; however, only 2.64% of patients were given pharmacological therapy. Following a hip fracture, the mortality rate was 18.5% at 1 year and 26.21% at 2 years. Apart from a high mortality rate, 28.19% of individuals sustained another fragility fracture before or after the hip fracture.Conclusion There should be increased osteoporosis awareness in Malta and a national bone mineral density screening program should be set up. An active role of the orthogeriatrics team in the management and treatment of osteoporosis following a fragility fracture might improve treatment rate and decrease refracture and mortality rates.
Keywords: hip fractures; fragility fractures; calcium; vitamin D; bisphosphonates